(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
This paper aims to show that cultural materials, which are often considered cultural and area-bounded, turn out to have a diversity that depends on each place’s social, cultural, economic, and geographical dynamics. This paper will focus on cultural materials in the form of Sumba weaving cloth. This paper is based on research with a qualitative approach, especially with observation methods in several weaving centers in Sumba and in-depth interviews with weaving artisans. The result of this study is that Sumba weavings cloth has local characteristics that depend on environmental potential, social, economic, historical, and cultural aspects, as well as the knowledge of its weavers from each region in Sumba. This diversity is reflected in the manufacturing techniques, coloring techniques, and various motifs adorn the weaving process.